Sistem Pemindaian Diameter Dalam Tangki Silinder Tegak Berbasis Ultrasound Ranging - sutanto, willi; Suprijanto; Juliastuti, Endang; Prihensa, Herfin Yienda; Gianto (Jurnal Otomasi Kontrol dan Instrumentasi, 2022)
Upright Cylindrical Fixed Measuring Tank (TUTSIT) is commonly used to store liquids of high economic value. TUTSIT needs to be calibrated periodically. For TUTSIT inner diameter scanning, a prototype ultrasound-based (US) ranging distance scanner has been developed with 3 US transducers with a frequency of 42kHz. For TUTSIT diameter scanning, two US transducers are mounted in a mechanical system that rotates 360o automatically and continuously. To determine the altitude position during scanning, one US transducer is mounted vertically facing vertically down on a tripod supporting the scanner's mechanical system. The scanner system was tested on a 75 kL capacity TUTSIT on course II of the 4 courses in the tank. The scanned data, which came from cloud points from course II, were pre-processed to be cleaned of outliers. The test results show that the system has functioned properly to measure the inner diameter of the tank at a height of 227 cm, 253 cm, and 261 cm. The scanning measurement error at a height of 227 cm and 253 cm is ±0.5% while at a height of 261 cm, the measurement error is about ±2.3%. The flatness of the prototype position greatly affects the accuracy of the diameter measurement, as can be seen from the measurement error at a height of 227 cm and 253 cm which is better than the measurement at a height of 261 cm, which does not pay attention to the flatness of the prototype position.